PERAN KEPALA MADRASAH SEBAGAI EDUCATOR UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI MBI AMANATUL UMMAH PACET MOJOKERTO - Ashari; Zakariyah (LPPM IAI Almuslim Aceh, 2024)
The results of the study show 1) the role of the head of the madrasa as an educator advises and encourages teachers to improve professional competence through further education, workshops, seminars, upgrading and training. The madrasa head guides teachers, encourages teachers to improve their skills in science and technology and becomes a good role model for all madrasa residents; 2) Teacher professional competence at MBI Amanatul Ummah. The teacher understands his obligation to be a good teacher or not at all. Many teachers have been certified, then received many awards from within and from outside, and the last education of many teachers is S2 and S3; 3) The obstacles are the distance between the teacher's house and the madrasa, the many teacher activities, and limited time due to the dense student activities. Meanwhile, those who support madrasa heads facilitate transportation, activities related to increasing teacher professional competence. In general, smart students. As well as giving prizes to the best teachers.